Neuroinflammation in the central nervous system: Symphony of glial cells - Yang, Qiao‐qiao; Zhou, Jia‐wei (Glia, 2019)
Neuroinflammation in the central nervous system (CNS) is an important subject of neuroimmunological research. Emerging evidence suggests that neuroinflammation is a key player in various neurological disorders, including neurodegenerative diseases and CNS injury. Neuroinflammation is a complex and well‐orchestrated process by various groups of glial cells in CNS and peripheral immune cells. The cross‐talks between various groups of glial cells in CNS neuroinflammation is an extremely complex and dynamic process which resembles a well‐orchestrated symphony. However, the understanding of how glial cells interact with each other to shape the distinctive immune responses of the CNS remains limited. In this review, we will discuss the joint actions of glial cells in three phases of neuroinflammation, including initiation, progression, and prognosis, the three movements of the symphony, as the role of each type of glial cells in neuroinflammation depends on the nature of inflammatory cues and specific course of diseases. This perspective of glial cells in neuroinflammation might provide helpful clues to the development of the early diagnosis and therapeutic intervention of the various CNS diseases. Main Points Neuroinflammation in the CNS is well orchestrated by different groups of glial cells and immune cells. Neuroinflammation reflects joint actions of glial cells in three phases of neuroinflammation, including initiation, progression and prognosis.